THE INFLUENCE OF FINANCIAL LITERACY, FINANCIAL ATTITUDE AND PEER INFLUENCE TOWARD RETIREMENT SAVING BEHAVIOR MODERATED BY GENDER: A CASE IN INDONESIA - Farida Komalasari; Rendi Zikri Mulyadi (Universitas Pasundan, 2023)
The purpose of this study is to determine the influence of financial literacy, financial attitude and peer influence with the moderation effect of gender and to analyze the differences in retirement saving behavior between male and female. The respondents of this study consists of 101 female and 101 male working individuals and were selected using non-probability sampling with purposive and snowballing techniques. The data collection instrument used was an online questionnaire. The data in this research were analyzed using One Way Analysis of Covariance (ANCOVA). The result showed that financial literacy influences retirement saving behavior with the moderation of gender, financial attitude influences retirement saving behavior with the moderation of gender, and peer influence influences retirement saving behavior with the moderation of gender. Another finding in this study was a difference between male and female working individuals in terms of their retirement saving behavior.